2002
DOI: 10.1188/02.onf.517-532
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Evidence on Symptom Management of Cancer-Related Anorexia and Cachexia

Abstract: Improved nutritional assessment skills are needed with an emphasis on anticipated problems and current status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 45 publications
0
48
0
2
Order By: Relevance
“…These behaviours include exercise [11], energy conservation/activity management [12], sleep hygiene [13], improved nutrition [14] and psychosocial strategies [15]. Of these self-care behaviours, exercise has undergone the most research in recent years though the efficacy of this approach requires further investigation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…These behaviours include exercise [11], energy conservation/activity management [12], sleep hygiene [13], improved nutrition [14] and psychosocial strategies [15]. Of these self-care behaviours, exercise has undergone the most research in recent years though the efficacy of this approach requires further investigation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For those at risk for unintentional weight loss, multifaceted interventions should focus on increasing food intake and reducing total energy expenditure to achieve a positive energy balance and thereby increase weight. 26 Physical activity may be useful to the underweight survivor when tailored to provide stress reduction and to increase strength, but high levels of physical activity make weight gain more difficult. 14 Obesity is a risk factor for some of the most common cancers in the United States, such as postmenopausal breast cancer and colorectal cancer.…”
Section: Body Weightmentioning
confidence: 99%
“…Medications, omega-3 fatty acid supplements, and additional nutritional support may be helpful for those experiencing weight loss. 26 If nutrient deficiencies are present or survivors cannot eat enough to adequately meet micronutrient needs, a multivitamin-mineral supplement is advisable, either in pill or liquid form.…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…13 A weight loss greater than 10% in the previous 6 months was identified in 38% of patients with gastric cancer, 26% of patients with pancreatic cancer, 15% of patients with lung cancer, 14% of patients with colon cancer, and 6% of patients with breast cancer. 14 An early prospective study of head and neck cancer patients showed that 38% of those with a nutritional deficit have a 2-year survival of only 7.5% compared with more than 57% in the remainder of the cohort. 15 Research, to date, focused on the prevalence and incidence of changes, but little empirical work has been undertaken to understand how patients manage these changes.…”
mentioning
confidence: 99%